Relationship Between Health Worker Support and Youth Activity Integrated Youth Service Posts in Purwosari, Surakarta - Francysca Tiara Fitra Narantika; Kusuma Estu Werdani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Adolescent Integrated Service Post is one of the health efforts that play an important role in improving the quality of adolescent health. However, adolescent participation in posyandu activities is often low. The support of health workers is considered an important factor that can influence the level of activeness of adolescents in these activities. This study aims to determine the relationship between health worker support and adolescents' activeness in Youth Posyandu in Purwosari Village, Surakarta. This study used a quantitative research design with a cross-sectional approach. The population of this study were 818 adolescents aged 15-19 years in Purwosari Village, Laweyan District, Surakarta City. The sample of this study was 80 adolescents using snowball sampling technique. Data were collected through questionnaires. Data analysis was performed using the chi-square statistical test to see the relationship between variables. The results showed that there was a significant relationship between health worker support and teenagers' activeness at the Youth Integrated Service Post in Purwosari, Surakarta (p-value=0.023). The highest value was when leaders and health workers visited adolescents, and adolescents, and the lowest value was when leaders and health workers only persuaded adolescents to participate in the programs of the Youth Integrated Service Post. Most adolescents have a regular intention to join the Integrated Youth Service Post programs. Recommendations that researchers can give to health workers are to share good information and invite adolescents to be active in the Integrated Service Post for Adolescents. Keywords : Activeness, Adolescents, Health worker support, Integrated service